The 4G/5G Polymorphism in the Plasminogen Activator Inhibitor-1 Gene Is not Associated with Myocardial Infarction - Doggen, C. J. M.; Bertina, R. M.; Cats, V. Manger; Reitsma, P. H.; Rosendaal, F. R. (Thrombosis and Haemostasis, 1999)
Several studies have found an association between high plasminogen activator inhibitor-1 (PAI-1) levels and myocardial infarction. Whether this is causal or a consequence of atherosclerosis or tissue damage, remains unclear. Homozygous carriers of the 4G allele of the 4G/5G polymorphism in the PAI-1 gene have higher PAI-1 levels compared to carriers of the 5G allele in healthy persons in some studies, but not all. If PAI-1 levels are causally related to myocardial infarction, one would expect more homozygous carriers of the 4G allele among patients, provided that these carriers have high PAI-1 levels among healthy persons in that population. We investigated the distribution of this polymorphism in the “Study of Myocardial Infarctions Leiden” (SMILE), including 331 men with a myocardial infarction and 302 control subjects and measured PAI-1 antigen levels among the latter. Secondly, we looked into the association of cardiovascular risk factors with PAI-1 levels.We did not find an increase in risk of myocardial infarction in carriers of the 4G allele. Neither did we find an association, nor a trend, between the 4G/5G polymorphism and PAI-1 antigen levels in control subjects. Controls with obesity, hypertension, or who smoked had significant higher PAI-1 antigen levels compared with persons without these factors. High cholesterol and triglyceride levels were also associated with high PAI-1 antigen levels, and HDL-cholesterol levels showed an inverse association.We conclude that the 4G/5G polymorphism in the PAI-1 gene is not associated with the risk of myocardial infarction. As we did not find any association between this polymorphism and PAI-1 antigen levels in healthy persons, we cannot draw any conclusions about the causality of PAI-1 itself for myocardial infarction.